Low-Level Cues and Ultra-Fast Face Detection - Crouzet, Sébastien M.; Thorpe, Simon J. (Frontiers in Psychology, 2011)
Recent experimental work has demonstrated the existence of extremely rapid saccades towards faces in natural scenes that can be initiated only 100 ms after image onset (Crouzet, Kirchner, & Thorpe, 2010). These ultra-rapid saccades constitute a major challenge to current models of processing in the visual system because they do not seem to leave enough time for even a single feed-forward pass through the ventral stream. Here we explore the possibility that the information required to trigger these very fast saccades could be extracted very early on in visual processing using relatively low-level amplitude spectrum (AS) information in the Fourier domain. Experiment 1 showed that AS normalization can significantly alter face detection performance. However, a decrease of performance following AS normalization does not alone prove that AS-based information is used (Gaspar & Rousselet, 2009). In Experiment 2, following the Gaspar and Rousselet paper, we used a swapping procedure to clarify the role of AS information in fast object detection. Our experiment is composed of 3 conditions: (i) original images, (ii) inverted, in which the face image has the AS of a vehicle, and the vehicle has the AS of a face, and (iii) swapped, where the face has the AS of another face image, and the vehicle has the AS of another vehicle image. The results showed very similar levels of performance in the original and swapped conditions, and a clear drop in the inverted condition. This result demonstrates that, in the early temporal window offered by the saccadic choice task, the visual saccadic system does indeed rely on low-level AS information in order to rapidly detect faces. This sort of crude diagnostic information could potentially be derived very early on in the visual system, possibly as early as V1 and V2.